Enable Flexible Spectrum Access with Spectrum Virtualization - Tan, Kun; Shen, Haichen; Zhang, Jiansong; Zhang, Yongguang (IEEE DySpan, 2012)
Enabling ﬂexible spectrum access (FSA) in existing wireless networks is challenging due to the limited spectrum programmability – the ability to change spectrum properties of a signal to match an arbitrary frequency allocation. This paper argues that spectrum programmability can be separated from general wireless physical layer (PHY) modulation. Therefore, we can support ﬂexible spectrum programmability by inserting a new spectrum virtualization layer (SVL) directly below traditional wireless PHY, and enable FSA for wireless networks without changing their PHY designs. SVL provides a virtual baseband abstraction to wireless PHY, which is static, contiguous, with a desirable width deﬁned by the PHY. At the sender side, SVL reshapes the modulated baseband signals into waveform that matches the dynamically allocated physical frequency bands – which can be of different width, or non-contiguous – while keeping the modulated information unchanged. At the receiver side, SVL performs the inverse reshaping operation that collects the waveform from each physical band, and reconstructs the original modulated signals for PHY. All these reshaping operations are performed at the signal level and therefore SVL is agnostic and transparent to upper PHY. We have implemented a prototype of SVL on a software radio platform, and tested it with various wireless PHYs. Our experiments show SVL is ﬂexible and effective to support FSA in existing wireless networks.e of SVL on a software radio platform, and tested it with various wireless PHYs. Our experiments show SVL is flexible and effective to support FSA in existing wireless networks.